2005
DOI: 10.1016/j.scitotenv.2004.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of mercury in the tissues of the common octopus Octopus vulgaris (L.) in two localities on the Portuguese coast

Abstract: Mercury concentrations were measured in tissues of 12 individuals of Octopus vulgaris, captured by the commercial fishery at two points along the Portuguese coast, Viana do Castelo and Cascais, in spring 2002. Concentrations were determined in six tissues (digestive gland, branchial hearts, gills, mantle, arms, and gonads). Correlations between mercury concentrations in different tissues were examined as were correlations between mercury levels and total length, mantle length, weight, gonadosomatic index, dige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
26
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 26 publications
8
26
1
2
Order By: Relevance
“…River flow regime and pyrite belt location were invoked as major factors influencing these differences. A similar geographic contrast was found for Zn, Pb, Cd and Hg concentrations in the digestive gland of Octopus vulgaris (Raimundo et al 2004, Napoleão et al 2005, Seixas et al 2005: enhanced levels of Pb, Hg, and Zn were found in individuals from the south coast and higher accumulation of Cd was found in specimens captured in NW stations.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…River flow regime and pyrite belt location were invoked as major factors influencing these differences. A similar geographic contrast was found for Zn, Pb, Cd and Hg concentrations in the digestive gland of Octopus vulgaris (Raimundo et al 2004, Napoleão et al 2005, Seixas et al 2005: enhanced levels of Pb, Hg, and Zn were found in individuals from the south coast and higher accumulation of Cd was found in specimens captured in NW stations.…”
Section: Introductionsupporting
confidence: 69%
“…Miramand & Bentley 1992, Nessim & Riad 2003, Seixas et al 2005, Bustamante et al 2008. Furthermore, accumulated Pb levels appear to depend on the availability of Pb in water and food (Bustamante et al 1998, Raimundo et al 2004, Napoleão et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The crabs of the Santos shelf showed the same pattern: larger species had higher δ 15 N values and were more contaminated than were smaller species. In cephalopods, Hg mostly accumulates in muscle; the degree of contamination is related to the size and sex of Loliginidae squid (Bustamante et al 2006 (Seixas et al 2005). For polychaetes, feeding modes and depth position in sediment are stronger predictors of Hg contamination than trophic position; burrowing deposit-feeding polychaetes bioaccumulate more MeHg than carnivores do (Sizmur et al 2013).…”
Section: Mercury In Organismsmentioning
confidence: 99%
“…The available information is very limited. Alkoxyalkyl compounds are absorbed by inhalation and by ingestion more efficiently than inorganic mercury salts (88). The distribution and excretion patterns of absorbed mercury follow those of inorganic mercury salts.…”
Section: Toxicity Of Organic Mercurymentioning
confidence: 96%